Epidemiology, Clinical Characteristics, and Associations for Rome IV Functional Nausea and Vomiting Disorders in Adults - Aziz, Imran; Palsson, Olafur S.; Whitehead, William E.; Sperber, Ami D.; Simrén, Magnus; Törnblom, Hans (Clinical gastroenterology and hepatology, 2019)
Functional nausea and vomiting disorders (FNVDs) are classified as chronic nausea and vomiting syndrome (CNVS) or cyclic vomiting syndrome (CVS)—CVS includes cannabinoid hyperemesis syndrome. We investigated the population prevalence of FNVDs, their characteristics, and associated factors. In the year 2015, an Internet cross-sectional health survey was completed by 5931 adults in the general populations of 3 English-speaking countries; 2100 participants were in the United States, Canada, or the United Kingdom. Quota-based sampling was used to generate demographically balanced and population-representative samples. The survey collected data on demographics, health care visits, medications, somatic symptom severity, quality of life, and symptom-based diagnostic criteria for Rome IV FNVDs as well as for irritable bowel syndrome and functional dyspepsia. Subsequent comparisons were made between Rome IV FNVD subjects and individuals without FNVDs (controls). Overall, 2.2% of the population (n = 131) fulfilled symptom-based diagnostic criteria for Rome IV FNVDs: the United States (3%) had a greater prevalence than Canada (1.9%) or the United Kingdom (1.8%) (P = .02). The prevalence of CNVS was similar among the countries, ranging from 0.8% to 1.2%. However, the prevalence of CVS was higher in the United States (2%) than in Canada (0.7%) or the United Kingdom (1%) (P = .03). The proportion of subjects with CVS taking cannabis did not differ significantly among countries (P = .31), although the 7 cases of cannabinoid hyperemesis syndrome were in the United States. A significantly higher proportion of subjects with CVS reported a compulsive need for hot water bathing to alleviate emetic symptoms than subjects with CNVS (44% vs 19%; P = .03); this behavior was independent of cannabis but augmented by its use. Subjects with FNVDs had significantly greater health impairment and health care utilization than controls. On multivariate analysis, independent factors associated with FNVDs were younger age, increasing somatic symptom severity, lower quality of life, presence of irritable bowel syndrome, and functional dyspepsia. However, on subgroup analysis, somatic symptom severity was associated with CVS but not CNVS, whereas poor quality of life was associated with CNVS but not CVS. Based on a cross-sectional health survey of adults in the general populations of 3 English-speaking countries, approximately 2% of subjects meet symptom-based criteria for Rome IV FNVDs and have considerable health impairments. Hot water bathing to alleviate emetic symptoms is reported for all FNVDs, and is perpetuated by cannabis use.